CO2 utilization through integration of post-combustion carbon capture process with Fischer-Tropsch gas-to-liquid (GTL) processes. (March 2017) - Rafiee, Ahmad; Panahi, Mehdi; Khalilpour, Kaveh Rajab
Graphical abstract: Abstract: Carbon capture is addressed as a medium term solution while industry and society are in their path towards future clean energies. However, in the absence of demand market and a revenue source for the recovered almost-pure CO2, the remained option, i.e. storage, does not seem to justify the economic feasibility of this climate change mitigation approach. In our current integration study, we consider existence of a Fischer-Tropsch Gas-to-liquid (GTL) plant in the vicinity of a fossil-fuel based power plant. The captured CO2 with post-combustion carbon capture technologies is fed into the GTL plants' reformer, i.e. a steam reformer or an auto-thermal reformer. We have presented a few case-studies based on optimal process simulation in Aspen Hysys software package. Unlike most of the studies, our objective is to maximize the wax production rate as upgrading could be carried out at demand market side. The results for a 300 MW coal-fired plant, and a GTL plant with the capacity of one train of Sasol Oryx GTL plant in Qatar show that an auto-thermal reformer (ATR) based GTL process does not have flexibility for CO2 intake, while all of the captured CO2 fed into the steam-methane reformer (SMR) process could be consumed. In summary, one train of Sasol Oryx GTL plant with a SMR reactor can utilize a net quantity of 105.5 tonnes-CO2 /h with subtracting the purged CO2 . The paper provides a detailed optimization-based data.